Gastronomi Jajanan Legendaris Sebagai Penguat Citra Destinasi Wisata Kuliner di Kota Malang - Sabrina, Arzendy Berlian; Krisnanda, Rulli; Saputri, Anggi Martiningtyas Januwati (Jurnal Kajian Pariwisata Dan Perhotelan, 2025)
This research explores the role of legendary street food in strengthening the culinary destination image of Malang City. As both an educational and tourism city, Malang has a rich culinary culture shaped by students and visitors. Using a qualitative descriptive approach, data were collected through in-depth interviews, direct observation, and documentation with the owners of legendary food establishments. The findings reveal that traditional culinary businesses such as Toko Oen, Putu Lanang, Ronde Titoni, and others not only offer authentic flavors but also carry strong cultural and historical values. These culinary icons contribute to building the gastronomic identity and emotional attachment of visitors, shaping a memorable experience that enhances destination loyalty. The study concludes that mapping and promoting legendary culinary heritage is essential in supporting sustainable gastronomic tourism and effective city branding in Malang.